EFFECT OF SYNCHRONIZATION OF CARBOHYDRATE AND PROTEIN SUPPLY IN THE SUGARCANE BAGASSE BASED DIET ON MICROBIAL PROTEIN SYNTHESIS IN SHEEP - Achmadi, J.; Suhada, A. T.; Nuswantara, L. K.; Wahyono, F. (Diponegoro University, 2016)
The experimental research was conducted to clarify the effect of synchronization of ruminal carbohydrate and protein releases from sugarcane bagasse based diet (SBBD) on microbial protein synthesis in sheep. The first experiment was the formulation of three SBBD with similar nutrient content but differed in synchronization indexes (namely 0.36; 0.50 and 0.63). The in sacco nutrient degradability coefficient was used to calculate the synchronization index of each feedstuff. The second experiment was determination of post feeding ruminal pH, ruminal concentrations of total volatile fatty acids (TVFA) and ammonia nitrogen (NH3-N), and blood urea nitrogen (BUN) level in sheep fed on experimental SBBD. The third experiment was determination of feed digestibility and estimation of microbial nitrogen synthesis (MNP) on the basis of excreted urinary allantoin. The alteration of dietary synchronization index did not change nutrient intake, but the digestibilities of DM, OM and CP were increased (P<0.05). The post feeding ruminal pH was decreased (P<0.05) but concentrations of post feeding ruminal TVFA and NH3-N, and level of BUN were increased (P<0.05) by the treatment of dietary synchronization index. The treatment of dietary synchronization index improved MNP (P<0.05), although dietary synchronization index at 0.63 lowered the MNP (P<0.05).